Leveraging digital technology for environment, social and governance (ESG) compliance - Ting, Fion Yee Jie (2025)
The construction industry plays a pivotal role in economic growth but is also one of the largest contributors to environmental degradation and social challenges. With rising global pressure to achieve sustainability and meet stricter regulatory demands, Environmental, Social, and Governance (ESG) compliance has become an essential benchmark for responsible construction practices. ESG compliance is increasingly critical in the construction industry, yet the integration of digital technologies to support ESG initiatives remains fragmented and limited to isolated applications. Thus, this study aims to examine how digital technologies can enhance ESG compliance, the challenges impeding their adoption, and the strategies to support implementation in Malaysia’s construction sector. A quantitative research approach was employed, with structured questionnaires distributed to construction professionals in Klang Valley, yielding 117 valid responses. The analysis employed Cronbach’s Alpha, the arithmetic mean, the Mann-Whitney U test, the Kruskal-Wallis test, and Spearman’s correlation. Results revealed that digital tools are perceived as highly effective in enhancing transparency, regulatory reporting, and energy efficiency; however, high implementation costs and workforce skill gaps were identified as critical barriers. Significant differences in perception emerged across professional roles and years of experience, highlighting diverse readiness levels for digital adoption. Correlation analysis further indicated strong linkages between digital upskilling and the successful deployment of ESG-focused technologies. The findings emphasise the need for a unified framework that integrates digital technologies into ESG practices, supported by industry-wide collaboration, government incentives, and standardized reporting mechanisms. This study contributes to advancing sustainable construction practices by offering practical recommendations for leveraging digital innovation to strengthen ESG compliance, thereby fostering accountability, resilience, and long-term competitiveness in the sector.